PENERAPAN METODE BRAIN BASED LEARNING PADA MATA KULIAH SEBAGAI UPAYA MENINGKATKAN KOMUNIKASI MATEMATIS DAN KETRAMPILAN BERPIKIR TINGKAT TINGGI MAHASISWA - Prihatin Ningsih Sagala (UIN Sumatera Utara Medan, 2014)
From the profile of data organizing the educational process at the Department of Mathematics Unimed indicates that the failure rate of repeat and students are still high, especially in the advanced course. In MatDis I know graduation percentage in 20012 s / d in 2013 that the gain value of A is still low at 17%, the value of B is 39%, 7% received C grades and 37% gaining grades E. One indication of the cause of this problem is a lack of communication skills and creative thinking mathematically solve students’ problem that is already supported by some of the concepts that have been previously known. If the issue is offered at the level theorem proving, students must start from where finish confusion. Moreover, at the level of analyzing the problem, questions synthesizing, solve problems, and evaluate the matter. The main objective of this research is to improve the skills of lecturers in applying the model to the course, specifically whether the application of the method of high-level questions on subjects MatDis I can improve mathematical communication and higherorder thinking students’ skill, this study included classroom action research. Based on the results obtained class action; for student participation was found that students who perform activities such as participation in rubric be on the score 1-5 contained 86%. The increase 77.7% overall. For the 86% graduation rate obtained from 36 or 31 students. And of the interview was obtained that 94% of students, or 34 of 36 people found the applied learning method is appropriate and suitable researchers in an effort to improve communication and mathematical thinking skill high level students.